2021
DOI: 10.1002/pts.2611
|View full text |Cite|
|
Sign up to set email alerts
|

A review of packaging‐related studies in the context of household food waste: Drivers, solutions and avenues for future research

Abstract: Packaging has the potential to reduce food waste and contribute to the United Nations sustainable development goal 12.3. Yet packaging is also a household food waste (FW) driver, necessitating packaging improvements. Through a review of primary consumer studies on household FW and packaging published 2006-2020, this study mapped the effects of packaging functions on different food categories to identify packaging-related FW drivers, solutions and research opportunities. Relevant studies are increasing, yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
(808 reference statements)
0
5
0
Order By: Relevance
“…Packaging contributes to decreasing FLW and the corresponding negative impact that producing and distributing uneaten or inedible food has on our environment and economy. FLW reduction is first a matter of packaging functionality (e.g., barrier properties) that maintain a modified atmosphere suitable for food preservation (e.g., avoid the remoistening of a crispy, dry product), 2 but also a matter of ease of use (e.g., individual‐serving portions, the packaging should be easy to open, to empty) 38 . Using packaging of individual serving sizes reduces the risk that leftovers from a larger family‐size package are incorrectly stored after the first use and finally never consumed and discarded 37,39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Packaging contributes to decreasing FLW and the corresponding negative impact that producing and distributing uneaten or inedible food has on our environment and economy. FLW reduction is first a matter of packaging functionality (e.g., barrier properties) that maintain a modified atmosphere suitable for food preservation (e.g., avoid the remoistening of a crispy, dry product), 2 but also a matter of ease of use (e.g., individual‐serving portions, the packaging should be easy to open, to empty) 38 . Using packaging of individual serving sizes reduces the risk that leftovers from a larger family‐size package are incorrectly stored after the first use and finally never consumed and discarded 37,39 .…”
Section: Resultsmentioning
confidence: 99%
“…properties) that maintain a modified atmosphere suitable for food preservation (e.g., avoid the remoistening of a crispy, dry product), 2 but also a matter of ease of use (e.g., individual-serving portions, the packaging should be easy to open, to empty). 38 Using packaging of individual serving sizes reduces the risk that leftovers from a larger family-size package are incorrectly stored after the first use and finally never consumed and discarded. 37,39 However, individual-serving packaging also uses more material proportionally to pack the same quantity of food and thus has a higher environmental impact than larger packages.…”
Section: Analysis Of the Literaturementioning
confidence: 99%
“…In the selected literature reviews can be found some reviews on food waste, such as the study published by Chan [56], which looks into packaging-related studies in the context of household food waste, or another of his studies [51], which explores the different packaging solutions available to address household food waste.…”
Section: Background Analysismentioning
confidence: 99%
“…Brennan et al (2021) performs its systematic review based on the discussion of academic and industrial food waste, focusing on packaging technologies as a way to promote the reduction of food waste in consumers' homes. In a similar study on packaging, Chan (2021) considers mapping functions of packaging across different food categories to identify packaging-related food waste drivers; as a result, the author suggests a greater variety of packaging sizes, labels and clearer dates to help reduce waste.…”
Section: Consumer Behaviour In Relation To Food Wastementioning
confidence: 99%